2018
DOI: 10.1021/acs.jpcc.8b01558
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathic Perovskite Solar Cells: Effect of Humidity during Fabrication on the Performance and Stability of the Device

Abstract: Methylammonium Lead Iodide (CH 3 NH 3 PbI 3 ) is the archetypical active component of perovskite solar cells, which stand out due to their impressive photovoltaic performance. A major drawback of CH 3 NH 3 PbI 3 is its rapid degradation in humid environments.In this work, we fabricate CH 3 NH 3 PbI 3 films and devices by solvent engineering in N 2 and in ambient conditions with different humidities. Their aging and degradation is monitored by optical absorption and impedance spectroscopy measurements under mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 36 publications
1
49
0
Order By: Relevance
“…This is especially true in the cases of intentional exposure to moisture during preparation in order to improve the grain morphology through solvent annealing. 38,39 Acknowledgement The authors thank Paolo Massimiliano Latino (ISM-Tor Vergata) for his technical assistance, Sara Notarantonio (ISM-Montelibretti) for the assistance in the synthesis, Marco Guaragno (ISM-Tor Vergata) for his technical support in X-ray experiments, Dr. Cristina Riccucci for the DTA-DSC measurements and Dr. Gloria Zanotti for fruitful discussions.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true in the cases of intentional exposure to moisture during preparation in order to improve the grain morphology through solvent annealing. 38,39 Acknowledgement The authors thank Paolo Massimiliano Latino (ISM-Tor Vergata) for his technical assistance, Sara Notarantonio (ISM-Montelibretti) for the assistance in the synthesis, Marco Guaragno (ISM-Tor Vergata) for his technical support in X-ray experiments, Dr. Cristina Riccucci for the DTA-DSC measurements and Dr. Gloria Zanotti for fruitful discussions.…”
Section: Introductionmentioning
confidence: 99%
“…[50] More recently, an interesting additive-antisolvent method under room conditions has been proposed by Yang et.al. [18,53] They found that perovskite prepared under higher %RH presents more robust resistance to degradation, attributing this robustness to the retained water molecules into the perovskite structure, which avoid further invasion of moisture (Figure 4d). They proposed an enhanced crystallinity lacking of pinholes and reduced hysteretic behaviour in devices prepared with their method, attributing this effect to a fast extraction of water molecules during the annealing step, as methanol has high water solubility.…”
Section: Effect Of H 2 O As Moisture In Ambient Atmospherementioning
confidence: 99%
“…At a similar conclusions arrived Contreras et.al analysing recently the effects of moisture during MAPbI 3 preparation. [18,53] They found that perovskite prepared under higher %RH presents more robust resistance to degradation, attributing this robustness to the retained water molecules into the perovskite structure, which avoid further invasion of moisture ( Figure 4d).…”
Section: Effect Of H 2 O As Moisture In Ambient Atmospherementioning
confidence: 99%
See 2 more Smart Citations